The importance of EZH2 and MOC‐31 expression in the differential diagnosis of benign and malignant effusions. Issue 2 (26th December 2016) - Sadullahoglu, Canan; Nart, Deniz; Veral, Ali
Abstract : Background: All malignant tumors may spread throughout the pleural, peritoneal, and pericardial cavities. The presence of tumor cells in serosal fluid is a poor prognostic indicator. It may be difficult to differentiate nuclear atypia of mesothelial cells due to injury of serosal surfaces from mesothelioma or malignant epithelial tumor cells. Epithelial and mesothelial immunohistochemical markers can be used in such conditions. The aim of this study was to evaluate the expression of two immunohistochemical markers (MOC‐31 and EZH2) in serosal effusions. Methods: The study included a total of 142 patients diagnosed with benign or malignant cytology between January 2012 and April 2014. MOC‐31 and EZH2 were applied to the cell blocks of 53 patients with benign cytology and 89 patients with malignant cytology determined based on the clinical, radiological data, histopathology diagnosis, and clinical follow‐up in the absence of any surgical material of the patient in the hospital archive system. Results: None of the benign cases showed MOC‐31 and EZH2 expression, although these markers were positive in 96 and 93% respectively of the malignant cases. Conclusion: In conclusion, it could be considered cost‐effective to use a double immunohistochemical antibody kit for these two markers, MOC‐31 membranous and EZH2 nuclear staining, in the diagnosis of malignant effusions. Diagn. Cytopathol. 2017;45:118–124. © 2016 Wiley Periodicals, Inc.